Religion and politics in the European Union : the secular canopy - Foret, François (Cambridge studies in social theory, religion, and politics, 2015)
This book analyzes the place and influence of religion in European politics. François Foret presents the first data ever collected on the religious beliefs of European decision makers and what they do with these beliefs. Discussing popular assumptions such as the return of religion, aggressive European secularism, and religious lobbying, Foret offers objective data and non-normative conceptual frameworks to clarify some major issues in the contemporary political debate.
Keywords: Church and state : European Union countries; Religion and politics : European Union countries; Religion and state : European Union countries; Secularism : European Union countries; EU-länder; EU-maat; politiikka; politik; religion och religioner; samhället; uskonto ja uskonnot; yhteiskunta